“They Need to Know the Science, but We also Need to Listen”: Perspectives of Black Rural Postpartum Mothers’ Health Care Providers And Support Persons - Natalie Hernandez-Green; Morgan V. Davis; Kaitlyn Hernandez-Spalding; Merna S. Beshara; Oluyemi Farinu; Kennedy Lewis; Sherilyn Francis; LeThenia Joy Baker; Sherrell Byrd; Andrea Parker; Rasheeta Chandler (Health Equity)
Background: In the United States, Black women are three times more likely to be affected by maternal mortality than White women. People who live in rural areas also face an increased risk. The objective of this study was to explore the perspectives of Black postpartum women’s support persons and health care providers, and the impact of race and rurality on their roles, to inform the development of a mobile health (mHealth) application focused on postpartum transitional care for rural Black women. Methods: Utilizing a semistructured designed discussion guide, we conducted four focus groups between July 2021 and October 2021. We asked support persons and health care providers to share their opinions about (1) postpartum needs, (2) the current hospital discharge process, (3) gender discrimination and experiences of racism and classism, and (4) suggestions for mobile application development. Results: Ten health care providers and seven support persons participated in the focus groups. A total of 57.1% of support persons identified themselves as a family member of the mother. In addition, 60% of health care providers indicated they practiced in a rural area at the time. Identified themes included race and rurality, emotional health, participants’ roles in relation to mothers’ needs, and the importance of technology for accessing information and resources. Conclusion: When describing their personal experiences, participants emphasized the importance of mHealth technology for helping Black postpartum mothers access health information. Insight from support persons and health care providers highlighted the challenges Black rural mothers face during the postpartum period and how our mobile application can be best utilized to address their needs.